MIKHAIL M. ODINTSOV’S EXHIBITION IN THE MUSEUM OF THE INSTITUTE OF THE EARTH’S CRUST - Larisa A. Ivanova (Геодинамика и тектонофизика)
The Museum of the Institute of the Earth’s Crust opened an exhibition devoted to Mikhail M. Odintsov (1911–1980), the prominent Russian geologist and the corresponding member of the USSR Academy of Sciences, who headed the Institute of the Earth’s Crust from 1954 to 1976. He was among researchers who pioneered in discovering diamonds in Siberia, Russia. He determined promising diamondbearing areas in Yakutia. The kimberlitic nature wad established, and the diamondiferous kimberlite prospecting method was developed. Prospective diamondbearing capacities were forecasted for the southern part of the Siberian platform and the Prisayanie. The Angara-Vilui ore belt was defined as the largest mineragenic sub-province in the southern East Siberia. The exhibition was opened on 07 November 2011 when the All-Russia Conference devoted to the 100th anniversary of Mikhail M. Odintsov took place in Irkutsk. It presents photographs, personal belongings and documents that provide information about Mikhail M. Odintsov’s childhood and youth years, pedagogical activities, field studies, researches, multidiscipline scientific organization, social and political activities. A collection of kimberlite samples from Yakutia and beyond supports the exposition. A model of the Mir kimberlite pipe is presented; it is the first diamondiferous kimberlite found in June 1955 and developed in Siberia.